2016
DOI: 10.3390/insects7030039
|View full text |Cite
|
Sign up to set email alerts
|

Lariophagus distinguendus (Hymenoptera: Pteromalidae) (Förster)—Past, Present, and Future: The History of a Biological Control Method Using L. distinguendus against Different Storage Pests

Abstract: Legal requirements and consumer demands for residue-free products pose a big challenge for pest control in grain stores. One possible alternative to chemical insecticides is biological pest control with the pteromalid wasp Lariophagus distinguendus against the weevils Sitophilus granarius, S. oryzae (Coleoptera: Dryophtoridae), and many other storage pest beetles. The use of this wasp as a biocontrol agent was already suggested in 1919 by Prof. Dr. Hase [1]. Despite many studies on host-finding and behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Our study revealed that L. distinguendus , a parasitoid which occurs in human environments and has been studied for a long time (Niedermayer et al, ), consists of at least two different species. These species are reproductively separated by (a) ecological isolation, (b) almost absolute sexual isolation due to female mate choice, (c) postzygotic isolation due to CI caused by a yet undescribed endosymbiotic bacterium, (d) and other, hitherto unknown barriers.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our study revealed that L. distinguendus , a parasitoid which occurs in human environments and has been studied for a long time (Niedermayer et al, ), consists of at least two different species. These species are reproductively separated by (a) ecological isolation, (b) almost absolute sexual isolation due to female mate choice, (c) postzygotic isolation due to CI caused by a yet undescribed endosymbiotic bacterium, (d) and other, hitherto unknown barriers.…”
Section: Discussionmentioning
confidence: 64%
“…Our study revealed that L. distinguendus, a parasitoid which occurs in human environments and has been studied for a long time (Niedermayer et al, 2016), consists of at least two different species.…”
Section: Con Clus Ionsmentioning
confidence: 85%
See 1 more Smart Citation
“…Besides, it has been also showed that an important parasitoid of L . serricorne , Lariophagus distinguendus Forster (Hymenoptera: Pteromalidae) 66 , mainly rely to the VOCs emitted by adult beetle feces when locating its host, stressing that the potential impact of the VOCs proposed for real-world use should be evaluated also on biocontrol agents of the targeted pest, to shed light on potential behavioural changes 67,68 . In this framework, the attractiveness of VOCs from the CMMs to L .…”
Section: Discussionmentioning
confidence: 99%
“…Lariophagus distinguendus (Förster, 1841), which also belongs to the family Pteromalidae, is an apparently well-studied cosmopolitan parasitoid of certain beetle species (Coleoptera) which feed on many stored products [21–22]. However, our recent research revealed the presence of at least two cryptic species with alternative host preferences and strongly different DNA sequences [2325].…”
Section: Introductionmentioning
confidence: 99%